Adsorption and structure of copper(II) complexes on a silica gel surface chemically modified with 2-aminothiazole - Dias Filho, Newton L. [UNESP] (Elsevier, 1999)
The isotherms of adsorption of CuX2 (X=Cl-, Br-, ClO- 4) by silica gel chemically modified with 2-aminothiazole were studied in acetone and EtOH solutions, at 25°C. The 2-aminothiazole molecule, covalently bond to the silica gel surface, adsorbs CuX2 from solvent by forming a surface complex. At low loading, the electronic and E.S.R. spectral parameters indicate that the Cu2+ complexes have a distorted tetragonal symmetry. The d-d eletronic transition spectra show that for ClO- 4 complex, the peak of absorption do not change for any degree of metal loading whilst for Cl- and Br- complexes, the peak maxima shift to higher energy with lower metal loading. © Elsevier Science Ltd.
Keywords: 2-Aminothiazole; Copper complexes; Copper complexes with 2-aminothiazole; Electron spin resonance; Isotherms of adsorption of CuX2; Modified silica gel